Nozzle test system for droplet deposition characteristics of orchard air-assisted sprayer and its application - Changyuan, Zhai; Chunjiang, Zhao; Xiu, Wang; Wei, Li; Wei, Li; Ruixiang, Zhu (International Journal of Agricultural and Biological Engineering, 2014)
In order to obtain nozzle droplet deposition characteristics for sprayer mechanical design and variable spraying control algorithms, a nozzle droplet deposition characteristics test system for air-assisted spraying was designed. The test system can supply a stable wind site with precisely controlled air speed whose speed control ranges from 2 m/s to 16 m/s with maximum relative error of 4.5%. It can spray out a certain amount of liquid pesticide with adjustable spraying pressure which can be controlled with high precision while the maximum relative error is only 1.33%. The distribution of droplet deposition can be collected and measured by using the acquisition device and a pesticide deposition optical measurement system. The experiment of two-dimensional nozzle flow measurement was carried out. The results show that nozzle flow distribution is uniform and symmetric with “double-hump” shape in the spray range. Multi-nozzle overlapped droplet deposition ranges from 85% to 116% relative to the average. The nozzle droplet deposition experiment was completed. The experiment results show that in air-assisted spraying, the higher the wind speed, the less droplet deposition is affected by gravity. When the wind speed is higher than 12 m/s and spraying distance is 0.80 m, droplet deposition is concentrated on the originally designated point and hardly affected by gravity. The horizontal spray width becomes smaller with higher wind speed. When the wind speed is high, it can be considered that nozzle deposition only focuses on the nozzle center, if the position requirement is not very high in orchard spraying. Keywords: air-assisted spraying, orchard sprayer, flow distribution, droplet deposition, nozzle test system, characteristics test system DOI: 10.3965/j.ijabe.20140702.015 Citation: Zhai C Y, Zhao C J, Wang X, Li W, Li W, Zhu R X. Nozzle test system for droplet deposition characteristics of orchard air-assisted sprayer and its application. Int J Agric & Biol Eng, 2014; 7(2): 122－129.